Pengaruh Brand Image dan E-Service Quality Terhadap Keputusan Pembelian Melalui Kepuasan Konsumen Online Travel Agent Tiket.com - Indriyati, Indriyati; Sitorus, Marthaleina Ruminda; Tarina, Fransiska (Institut Transportasi dan Logistik Trisakti, 2022)
Online travel agents are increasingly in demand in line with the needs of society in the digital era who tend to want everything to be done practically. Purchasing decisions taken by consumers is an important factor in maintaining the existence of the company. This study aims to discuss how brand image and e-service quality influence consumer purchasing decisions through consumer satisfaction as an intervening variable at the online travel agent tiket.com using the Partial Least Square (PLS) research method with a total of 210 respondents. Based on the results of data processing, it can be concluded that brand image has a positive and significant influence on consumer satisfaction. E-service quality has a positive and significant influence on customer satisfaction, the better the quality of online services provided by the company, the higher the level of customer satisfaction and previous consumer transactions have an effect on subsequent consumer purchasing decisions, on the brand image variable, namely ticket reputation ticket.com among the public, in the e-service quality variable, namely the products offered by tiket.com are incomplete when compared to online travel agents.